PROFILE OF STUDENT’S MISCONCEPTIONS TOWARDS LEARNING SCIENCE - Wike Kusuma Wardani; Ummu Kulsum (PROSIDING SEMINAR KIMIA, 2015)
Students' understanding of science can lead to misconceptions. This study aimed to describe profile of student’s misconceptions towards learning science. Based on data ofstudents misconceptions on learning science, will be formulated students learning process. The participants of this research were students of class VII A in Public Junior High School 5 Surabaya. Student’s misconceptions were determinedbased on the results of understanding on learning science tests that was designed in the form of CRI (Centainty of Response Index). Verification of high intensity misconceptions was done by identifying misconceptions in groups. Data for identification of misconceptions in the group was based on the average value of CRI of respondents who answered correctly (CRIB), respondents who answered incorrectly (CRIS), and the fraction of respondents who answered correctly (Fb). The results of this study were (1) 16 items from 26 (61.5%) was misconceptions, and (2) misconceptions students with high intensity occurred in the concept of the use of reasoning, experimentation, the nature of scientific ideas, scientific ideas democratically, the task of scientists, nature scientists, science is a boring science, the ability of students to learn science, and the students' understanding of the philosophy of science.